Aspects de la recherche paysagère en Italie - Viviana Ferrario (Projets de Paysage)
This article proposes a brief incursion in the Italian contemporary landscape research. After a presentation of the historical, academic and institutional context, some points of reference for a first general orientation among its top protagonists, its various disciplinary approaches and its different themes are given to the reader. In conclusions some considerations on the very concept of research on landscape.